Effective Treatment of Simultaneous Distal Radius and Scaphoid Fractures - Blackburn, Julia; Johnson, Nick; Pocnetz, Sasa; Lindau, Tommy R. (Journal of Wrist Surgery, 2021)
Background There is an increasing trend for most surgeons to choose open reduction and internal fixation of simultaneous distal radius and scaphoid fractures; however, it is not clear if there is any evidence to support this.Case Description The purpose of this systematic review was to investigate the evidence for management of simultaneous distal radius and scaphoid fractures.Literature Review We performed searches of the EMBASE and MEDLINE databases (CRD42020167403). We included a total of 20 studies, involving 178 patients with 182 simultaneous fractures of the distal radius and scaphoid. The distal radius fractures were mostly intra-articular (112/182). The scaphoid fractures were mostly undisplaced (120/148) and at the scaphoid waist (152/178). All distal radius fractures went on to unite, and just 2 of 182 scaphoid fractures went on to nonunion. All included studies were retrospective case series, and therefore all were found to have a critical risk of bias due to confounding. The union rate for both the distal radius and scaphoid fractures is high with both operative and nonoperative treatments.Clinical Relevance Although there are no comparative studies to evaluate the most effective treatment, there is evidence to support operative management.Level of Evidence This is a Level IV, systematic review study.
Keywords: distal radius fractures; scaphoid fractures; simultaneous fractures; systematic review